2023
DOI: 10.1037/sgd0000563
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in rates of depression, anxiety, and suicidality among cisgender sexual minority and heterosexual college students.

Abstract: Sexual minority college students experience higher rates of depression, anxiety, and suicidality compared with their heterosexual peers. Significant social progress has been made in the last few decades, such that attitudes and policies toward sexual minorities in the United States have improved dramatically. It is unclear, however, whether this progress has decreased disparities in mental health outcomes between cisgender sexual minorities and heterosexuals. Therefore, the current study sought to determine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…During this period, people's mental health was affected by disruptions in people's spiritual life. Numerous studies have demonstrated that student depression and related health problems are increasing at a record rate (Pellicane & Ciesla, 2022). Meanwhile, surveys by many researchers show that the new habits of students that begin during this time have many good and bad sides.…”
Section: The Status Of Studentsmentioning
confidence: 99%
“…During this period, people's mental health was affected by disruptions in people's spiritual life. Numerous studies have demonstrated that student depression and related health problems are increasing at a record rate (Pellicane & Ciesla, 2022). Meanwhile, surveys by many researchers show that the new habits of students that begin during this time have many good and bad sides.…”
Section: The Status Of Studentsmentioning
confidence: 99%
“…Therefore, numerous specific elements contribute to achieving internal balance to different degrees, with physical and mental harmony being the most important aspects. Affected by drastic changes in social background, mental health problems are increasingly appearing in the lives of ordinary people, especially adolescents, and have attracted the attention of many scholars in recent years [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…In the general literature on college retention, mental health concerns like symptoms of depression, psychosocial stressors, and harmful substance use predict dropping out of college at all phases of enrollment (Thomas et al, 2021). Research examining SGM college student mental health has found that these students experience high minority stress and are at increased risk for poor mental health and psychological distress (Gonzales et al, 2016;O'Neill et al, 2022;Pellicane & Ciesla, 2022). Results from multiple iterations of the National College Health Assessment also indicate that SGM students experience a relatively higher rate of mental health concerns than their peers and are more likely to utilize mental health services (American College Health Association, 2022; Blosnich & Bossarte, 2012;Brittain & Dinger, 2015;).…”
Section: Introductionmentioning
confidence: 99%